EFEKTIVITAS PEMBERIAN INFUSED WATER KURMA TERHADAP PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI KEBIDANAN POLTEKKES MEDAN TAHUN 2020 - HIJRA HIDAYANA; Suswati Suswati (Poltekkes Kemenkes Medan, 2020)
Hemoglobin is the red pigment-protein contained in red blood cells. The function of hemoglobin is to transport oxygen from the lungs and in the bloodstream to be carried to the tissues. Hemoglobin can increase by increasing the intake of iron in the body. One way to increase hemoglobin can be done by giving method Infused Water Dates. Infused water is a drink consisting of plain water with fresh fruit added and soaking or settling together for a certain time. The making of infused water is carried out by soaking for a period of 0 to 12 hours, so that the infused water becomes a liquid medium that carries more nutrients than ordinary water and will be more easily absorbed by cells and distributed throughout the body (Sidauruk, 2018 ). In several studies, it is stated that dates can increase hemoglobin levels in the blood. Where dates contain iron, vitamin A, vitamin C, protein to form red blood cells. With the method, Infused Water the date palm water becomes alkaline so that it can accelerate the absorption process in the body. The purpose of this study was to determine the effectiveness of dates infused water provision to increase hemoglobin levels of midwifery adolescent girls at Medan Health Polytechnic in 2020. This research was quasi-experimental study using the One Group Pretest-Posttest Without Control Design approach. The sample in this study were 20 respondents of midwifery adolescent girls from Medan Health Polytechnic, using the technique of purposive sampling. The statistical test used wa the Wilcoxon Signed Rank Test because the data was not normal. The results of the Wilcoxon Signed Rank Test obtained the value of P-Value = 0.001. So it can be concluded that the date infused water is effective in increasing hemoglobin levels of midwifery adolescent girls at Medan Health Polytechnic in 2020. Keywords: Dates Infused Water, Increased Hemoglobin Levels, Girls Adolescent